Tourism Education Curriculum Adaptation Strategy in Facing Technological Developments and Digitalization - Rizki Sumardani; Bagas Anggara; Muharis; Fardiatunisa; Dwi Ananda (ESENSI: Jurnal Riset Pendidikan, 2025)
Technological developments and digitalization have brought transformative changes to the global tourism industry landscape. From digital marketing, online reservations, augmented reality (AR) and virtual reality (VR) based traveler experiences, to big data analytics for service personalization, the tourism sector is now heavily reliant on digital innovation. This phenomenon requires tourism education to adapt proactively to produce relevant and job-ready graduates. This research aims to identify and analyze the adaptation strategy of the tourism education curriculum in facing the challenges and opportunities posed by technological developments and digitalization. Using a qualitative approach with a case study method, data was collected through in-depth interviews with key stakeholders (academics, industry practitioners, and alumni) as well as analysis of curriculum documents from several leading tourism educational institutions. The results of the study indicate that effective curriculum adaptation strategies include the integration of digital-oriented courses, improving lecturers' competencies in digital literacy, developing technology learning facilities, and strengthening collaboration with industry. The main challenges faced are resistance to change, resource limitations, and the dynamic pace of technological development. The implications of this study emphasize the urgency of adapting a sustainable curriculum to ensure the relevance of graduates in the increasingly digital tourism job market.